ETHNOBOTANICAL STUDY OF MEDICINAL FLORA IN BALODABAZAR-BHATAPARA DISTRICT OF CHHATTISGARH - SHOBHANA KOSHLE; DEEPA BISWAS (The Bioscan, 2026)
The present ethnobotanical study was to record and describe the local and tribal medicinal plant knowledge of local and tribal community of the Balodabazar-Bhatapara district, Chhattisgarh, India. The focus of the study was to name and document the medicinal flora, their use in treatment, parts of the plants used, mode of preparation and mode of administration. The 20 villages were sampled using structured questionnaires and 55 informants (such as traditional healers, farmers, and the elderly residents) were interviewed to gather ethnobotanical data. The total number of medicinal plant species identified was 73 species of 67 genera and 37 families with Fabaceae, Euphorbiaceae and Lamiaceae being the most predominant families. Most of the species recorded were trees (46.58%), then herbs (27.40%), climbers (15.07%) and shrubs (10.96%). The most commonly used parts of the plants were the bark (19.23%), leaves (17.95) and roots (16.67). The major ways of preparation were decoctions (28.77%) and pastes (23.29%) and the most common administration routes were oral (42.47%) and topical (26.03%). Conservation evaluation showed that 60.27 percent of the species were defined as Not Evaluated (NE), and ecological and conservation research is in dire need. The results highlight the abundance of ethnomedicine and biodiversity of the area, which signifies a strong culture that depends on plants as medicine. Nevertheless, the threat to this traditional knowledge and biodiversity is produced by the growing levels of modernization and unsustainable harvesting actions. The paper identifies the necessity of community-based conservation practices, planting of medicinal species that are in demand and scientific validation of the traditionally used plants. The ethnobotanical data recorded makes a valid basis towards further pharmacological/phytochemical studies in the future to find new bioactive substances and enhance sustainable use of local medicinal plants. Keywords Traditional knowledge, Ethnomedicine, Phytochemical potential, Conservation status, Tribal communities.